The Artificial Intelligence-Powered Evolution of Human Resources: Transforming Workplaces for the Future - Shaikh, Faiyaz (Digital Repository of Theses, 2025)
This research investigated the integration of automation in Human Resource Management to align with the evolving future of work. It examines the impact that automation has on human resource functions which include recruitment, training, employee engagement, and performance management. This research adopted a mixed-methodology, wherein quantitative surveys with 350 human resource professionals were conducted in tandem with semi-structured qualitative interviews involving 15 participants. The quantitative data in this case was instrumental in showcasing the level of automation adoption and its underlying benefits, whereas the qualitative data helped in offering insights into organisational adjustments and personal experiences. The findings from this research revealed extensive implementation of automation within diverse industry sectors, wherein 72.6% of organisations surveyed adopted AI tools. The findings further revealed that the level of efficiency was increased along with innovation, however there continued to be challenges such as resistance to change and skill gaps. Based on the findings, it was concluded that strategic incorporation of automation with human resources nurtured agility and innovation, which helps in tackling the demands of future workforce. This research offered a roadmap for organisations to effectively maneuver transformations in human resources, while sustaining ethical aspects and nurturing readiness amongst workforce.